Nonlinear system optimization of cutting tools with dynamic vibration absorbers in deep hole boring: A stability analysis - Lie Li; Yuchen Ren; Zikai Shen; Junna Lu; Linhai Tong (Alexandria Engineering Journal)
Deep hole boring vibrations pose challenges due to low stiffness of long cantilever bars, impacting accuracy and standards. Nonlinear modeling provides deeper insights into chatter. Integrating dynamic vibration absorbers enhances boring bar stability. In this study, a nonlinear model is developed to investigate the vibration stability of the boring process, with the model's dimensionless parameters analyzed and solved using the Runge-Kutta method. The impact of nonlinear parameters associated with the damping and stiffness of the absorbers on the vibration characteristics of boring bars is thoroughly examined. The findings reveal that there exists an optimal range for the damping and stiffness of the absorbers, where vibration amplitude is significantly reduced, especially under conditions of high excitation force. Moreover, it is demonstrated that the introduction of cubic stiffness elements can further diminish vibration amplitude. These results offer valuable guidance for the design and optimization of DVA in deep hole boring, contributing to improved machining performance and accuracy.